Sodium Nitroprusside as a Hyperinflation Drug and Therapeutic Alternatives. (August 2018) - Cobb, Alex; Thornton, Luciana
Sodium nitroprusside (SNP) is a generically available and rapid-acting intravenous (IV) vasodilator that has been used clinically for decades. Prior to 2013, the cost of SNP was relatively low, and SNP was an affordable option for the treatment of acute hypertension. However, from 2013 to 2017, average wholesale prices for SNP rose to as high as US900 per vial, earning the drug its status as a "hyperinflation drug." Hyperinflation drugs pose a significant challenge for pharmacy departments. A multidisciplinary effort involving stakeholders from many backgrounds, including pharmacists, physicians, and nurses, is key to developing an effective cost containment strategy. A therapeutic interchange, wherein a drug with similar efficacy is substituted for another, is often an appropriate strategy to address rising drug costs. Fortunately, alternative drugs with a solid evidence base exist for the management of acute hypertension. The dihydropyridine calcium channel blockers, clevidipine and nicardipine, are IV titratable antihypertensive agents with favorable pharmacokinetic and safety profiles. Various studies indicate that clevidipine and nicardipine are effective alternatives to SNP for indications including hypertensive crisis and postoperative hypertension. Some hospitals have reported significant cost savings without adverse outcomes by substituting clevidipine or nicardipine for SNP. This article is intended to serve as a review of the evidence for clevidipine and nicardipine as potential substitutes for SNP and to provide strategies to successfully implement this therapeutic interchange.